The influence of promotion mix on purchasing behavior in B2B markets: case of Tatu Holdings - Zondiwa, Phlincerose Sharmaine (Midlands State University, 2018)
The study aimed at evaluating the influence of promotion mix on purchasing behavior in B2B markets. The study was conducted at TATU Holdings, in the Harare province of Zimbabwe. The study mainly aimed at measuring the effects of the following variables, personal selling on product interest, sales promotion on increasing or decreasing sales and advertising on product awareness. Data in the study was mainly acquired through a mixed method approach conducted using an exploratory and descriptive research designs. Data was generated mostly through questionnaires and interviews with 30 TATU Holdings customers and 7 TATU Holdings employees who were both probabilistic and non-probabilistic sampled. The study findings revealed that personal selling has an impact on product interest; while, sales promotion influence sales of a company and lastly, advertising influence product awareness. The study recommended internet advertising since the world is going digital; a need to venture into other marketing and promotion strategies such as direct marketing, e-marketing, product promotions and lastly, financial and non-financial motivation to sales team such as sales’ bonuses, sales’ commissions and awarding holiday packages in order to successfully seed an effective team